Ultrafast Mid-IR Laser Scalpel: Protein Signals of the Fundamental Limits to Minimally Invasive Surgery - Amini-Nik, Saeid (Public Library of Science, 2010)
Lasers have in principle the capability to cut at the level of a single cell, the fundamental limit to minimally invasive procedures and restructuring biological tissues. To date, this limit has not been achieved due to collateral damage on the macroscale that arises from thermal and shock wave induced collateral damage of surrounding tissue. Here, we report on a novel concept using a specifically designed Picosecond IR Laser (PIRL) that selectively energizes water molecules in the tissue to drive ablation or cutting process faster than thermal exchange of energy and shock wave propagation, without plasma formation or ionizing radiation effects. The targeted laser process imparts the least amount of energy in the remaining tissue without any of the deleterious photochemical or photothermal effects that accompanies other laser wavelengths and pulse parameters. Full thickness incisional and excisional wounds were generated in CD1 mice using the Picosecond IR Laser, a conventional surgical laser (DELight Er:YAG) or mechanical surgical tools. Transmission and scanning electron microscopy showed that the PIRL laser produced minimal tissue ablation with less damage of surrounding tissues than wounds formed using the other modalities. The width of scars formed by wounds made by the PIRL laser were half that of the scars produced using either a conventional surgical laser or a scalpel. Aniline blue staining showed higher levels of collagen in the early stage of the wounds produced using the PIRL laser, suggesting that these wounds mature faster. There were more viable cells extracted from skin using the PIRL laser, suggesting less cellular damage. β-catenin and TGF-β signalling, which are activated during the proliferative phase of wound healing, and whose level of activation correlates with the size of wounds was lower in wounds generated by the PIRL system. Wounds created with the PIRL systsem also showed a lower rate of cell proliferation. Direct comparison of wound healing responses to a conventional surgical laser, and standard mechanical instruments shows far less damage and near absence of scar formation by using PIRL laser. This new laser source appears to have achieved the long held promise of lasers in minimally invasive surgery.